2022
DOI: 10.1109/tvt.2022.3193198
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of IOS-Assisted NOMA System With Channel Correlation and Phase Errors

Abstract: In this paper, we investigate the performance of an intelligent omni-surface (IOS) assisted downlink non-orthogonal multiple access (NOMA) network with phase quantization errors and channel estimation errors, where the channels related to the IOS are spatially correlated. First, upper bounds on the average achievable rates of the two users are derived. Then, channel hardening is shown to occur in the proposed system, based on which we derive approximations of the average achievable rates of the two users. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…An accurate asymptotic analysis of a STAR-RIS system over correlated channels constitutes an important question for further research. APPENDIX A First, the expectation of H t can be computed directly as We have proved the mathematical relationship between E[|ϖ t,i ||ϖ t,j |] and E[ϖ t,i ϖ * t,j ], ϖ ∈ {g, h} in [20], and the relationship is given in (10) and (11), where E[|ϖ t,i ||ϖ t,j |] and E[ϖ t,i ϖ * t,j ] are the (i, j) entry in matrices Rt and R t , respectively. Exploiting (10), (11) and (25), the variance of H t is obtained as in Proposition 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate asymptotic analysis of a STAR-RIS system over correlated channels constitutes an important question for further research. APPENDIX A First, the expectation of H t can be computed directly as We have proved the mathematical relationship between E[|ϖ t,i ||ϖ t,j |] and E[ϖ t,i ϖ * t,j ], ϖ ∈ {g, h} in [20], and the relationship is given in (10) and (11), where E[|ϖ t,i ||ϖ t,j |] and E[ϖ t,i ϖ * t,j ] are the (i, j) entry in matrices Rt and R t , respectively. Exploiting (10), (11) and (25), the variance of H t is obtained as in Proposition 1.…”
Section: Discussionmentioning
confidence: 99%
“…Since phase errors exist in reality[17], this assumption gives a lower bound on the outage probability[18]. Further, only two-bit phase adjustment can achieve the performance close to the lower bound in practice[19],[20] 4. In this letter, we assume dt < dr.…”
mentioning
confidence: 99%
“…To realize such a function, we need to carefully design these parameters to meet these requirements. In the literature, there are some initial investigations [79], [80]. The authors in [79] presented the impact of the number of possible phase shifts on the ergodic capacity for IOS-aided wireless communication systems.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that a small number of phase shifts are sufficient enough to realize the potential of the IOS. In [80], the authors considered an IOS-aided non-orthogonal multiple access (NOMA) setting. Their simulation and theoretical results showed that low-precision elements with only four phase shifts can achieve performance close to that of ideal continuous phase shifts.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption on the ideal coherent phase adjustment gives an upper bound on the system performance[33]. Furthermore, as proved in[34],[35], only two-bit phase shifting leads to the performance close to upper bound in practice 5. Similar to[36]-[38], it is assumed that the horizontal distances of different channels are much larger than the vertical distances and the heights of TXs, RISs and UEs are ignored 6.…”
mentioning
confidence: 99%